2020
DOI: 10.1051/e3sconf/202016502003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of DA-6 on Phosphorus and Potassium Uptakes of Tomato Seedlings under Cadmium Stress

Abstract: In order to study the effect of foliar DA-6 on the phosphorus and potassium content of tomato seedlings under cadmium stress, the pot experiment was used to cultivate ‘Zhongza 9’ tomato in 50 μmol/L CdCl2•2.5H2O nutrient solution. The effects of DA-6 at different concentrations (0, 10, 20, 30 and 40 mg/L) on the phosphorus and potassium uptakes of tomato seedlings under cadmium stress were studied. The results showed that when the DA-6 concentration was 20 mg/L, the phosphorus content in the root and stem of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The research of shan indicated that DA‐6 increase phosphorus and potassium content in tomato seedlings under Cadmium stress. Different from her research, this experiment studied the effects of DA‐6 on the growth and cadmium accumulation of tomato seedlings 21 …”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The research of shan indicated that DA‐6 increase phosphorus and potassium content in tomato seedlings under Cadmium stress. Different from her research, this experiment studied the effects of DA‐6 on the growth and cadmium accumulation of tomato seedlings 21 …”
Section: Introductionmentioning
confidence: 94%
“…Different from her research, this experiment studied the effects of DA-6 on the growth and cadmium accumulation of tomato seedlings. 21 Tomato (Lycopersicum esculentum) is an annual or perennial plant in the genus Solanum of the Solanaceae family and produces juicy berries. 22 The ripe, juicy berries of the tomato plant have a unique flavor and contain a variety of nutrients with anti-cancer and anti-aging effects, and are of medicinal value.…”
Section: Introductionmentioning
confidence: 99%